2008
DOI: 10.1016/j.bcp.2007.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of memantine on mitochondrial function

Abstract: Because NMDA complex and mitochondrial function are related, we hypothesized memantine would influence mitochondrial function. We addressed this in vitro by studying the effects of chronic and acute memantine exposures on mitochondrial function. For acute exposure experiments, mitochondria were isolated from NT2 cells and assayed for electron transport chain (ETC) enzyme function and peroxide production in buffers containing up to 60 uM memantine. For chronic exposure experiments, NT2 cells were maintained for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…In a vitro study, which evaluated the effects of memantine on mitochondrial function, McAllister et al (2008) demonstrated that acute and chronic memantine treatments similarly affected complex I (increased at high concentrations) and IV (decreased at high concentrations) activities and were detected a lower mitochondrial peroxide production rate with chronic exposure. In the present study, we showed that creatine kinase activity increased with memantine at low concentrations (5 mg/kg) and decreased at high concentrations (20 mg/kg) after acute treatment.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a vitro study, which evaluated the effects of memantine on mitochondrial function, McAllister et al (2008) demonstrated that acute and chronic memantine treatments similarly affected complex I (increased at high concentrations) and IV (decreased at high concentrations) activities and were detected a lower mitochondrial peroxide production rate with chronic exposure. In the present study, we showed that creatine kinase activity increased with memantine at low concentrations (5 mg/kg) and decreased at high concentrations (20 mg/kg) after acute treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, clinical studies suggest that administration of memantine ameliorates depressive symptoms in patients suffering from major depression (Muhonen et al 2009;Ferguson and Shingleton 2007). Moreover, memantine alters mitochondrial function (McAllister et al 2008). Furthermore, glutamate neurotoxicity is associated with mitochondrial dysfunction (Almeida et al 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Multiple other sites of action have been reported for each drug (e.g., [26,71,72]). For example, memantine inhibits multiple acetylcholine receptors subtypes [73-76] and 5-HT 3 serotonin receptors [10,77], whereas ketamine binds to dopamine D2 and 5-HT 2 serotonin receptors [12,78] and to HCN1 channels [79].…”
Section: Mechanistic Bases For Differential Effects Of Memantine and mentioning
confidence: 99%
“…Intracellular Ca 2Ď© Measurement-To measure [Ca 2Ď© ] i in VSMCs after 48 h of treatment (24), cells were incubated with Fluo-4 AM (10 M; Invitrogen) for 25 min at room temperature. Fluorescence images were captured and analyzed using an inverted epifluorescence microscope (Nikon TE200) with a 40Ď« Plan Fluor objective, a high speed wavelength switcher (Lambda DG-4 from Sutter Instrument), a PC-controlled digital CCD camera (Hamamatsu C4742-95), and MetaMorph software (Universal Imaging).…”
Section: Methodsmentioning
confidence: 99%